2017
DOI: 10.1177/1049732317723889
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing and Responding to the “Toxic” Work Environment: Worker Safety, Patient Safety, and Abuse/Neglect in Nursing Homes

Abstract: This grounded theory study examined how the certified nursing assistant (CNA) understands and responds to bullying in the workplace. Constant comparative analysis was used to analyze data from in-depth telephone interviews with CNAs ( N = 22) who experienced bullying while employed in a nursing home. The result of the analysis is a multistep model describing CNA perceptions of how, over time, they recognized and responded to the "toxic" work environment. The strategies used in responding to the "toxic" environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 34 publications
(40 reference statements)
4
45
0
Order By: Relevance
“…Difficulties in defining abuse in nursing home settings have been found in studies that include staff's perceptions [39,54], where abusive situations are seen as normal in the nursing home culture [17,33,39,55]. However, these studies did not specifically focus on care managers' or leaders' understandings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Difficulties in defining abuse in nursing home settings have been found in studies that include staff's perceptions [39,54], where abusive situations are seen as normal in the nursing home culture [17,33,39,55]. However, these studies did not specifically focus on care managers' or leaders' understandings.…”
Section: Discussionmentioning
confidence: 99%
“…Good leadership plays a key role in developing staff's understanding of residents' needs [31,32] and creating a strong safety culture of respect, dignity, and quality [6,7,9,33]. The importance of leadership in developing a patient safety culture is highlighted in a report from the National Patient Safety Foundation [10].…”
Section: Introductionmentioning
confidence: 99%
“…The workplace environment can be classified into two major categories: collaborative workplace environment and toxic workplace environment. The collaborative workplace environment yields a sense of happiness, joy, harmony, kindness, politeness, cooperation, and facilitation at the workplace [ 19 , 20 ]. The workplace is toxic when individuals in power are greedy and narcissistic and/or use unfair means to bully, harass, threat, and humiliate others.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Disruptions in work can result in decreased patient outcomes through negative state anxiety stress, impaired communication and teamwork, and medical errors. [13,14,[24][25][26][27] In turn, medical errors and poor patient outcomes can generate serious financial burdens for organizations, with projected costs across Western Europe and the United States reaching $383 BN USD by the year 2020. [28] Likewise, a comparative study of the United States, Australia, New Zealand and Canada found turnover costs ranging between $20,561 USD -$48,790 USD.…”
Section: Disruptive Behaviorsmentioning
confidence: 99%